Design optimization of hybrid material B-pillar under crush loading - Öztürk, İsmail (Walter de Gruyter GmbH, 2024)
B-pillars are vital structural components in rollover-related accidents. In this study, the performances of homogeneous B-pillars designed from B1500HS-T25, AA2024-T351, and AA6061-T6 materials and hybrid B-pillars designed from their combinations under crushing load were compared in energy absorption using simulation results. Optimization studies were conducted utilizing the upper part B1500HS-T25 and lower part AA6061-T6 hybrid B-pillar, which gave the highest energy absorption value. Method of feasible directions was utilized to solve the single-objective optimization, and B-pillar mass decreased by 22.6 »>% from 2.736 to 2.117 »>kg compared with the reference B-pillar. Global Response Search Method and Multi-Objective Genetic Algorithm were used to solve the multi-objective optimization problem. B-pillar with min mass decreased mass value by 25 »>% from 2.736 to 2.052 »>kg for both methods. This optimum hybrid B-pillar can be utilized in car design. © 2023 Walter de Gruyter GmbH, Berlin/Boston.
Keywords: B-pillar; crush loading; energy absorption (EA); hybrid material; optimization